2005
DOI: 10.1111/j.1365-2842.2004.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparison between pains, difficulties in function, and associating factors of patients in subtypes of temporomandibular disorders

Abstract: The aim of this study was to compare the multidimensional properties among subtypes of painful temporomandibular disorders (TMD): myofascial pain (group I), disc displacement (group II), arthralgia (group IIIa) and osteoarthritis (group IIIb). A total of 511 patients answered a battery of questionnaires, which included questions relating to intensity and duration of pain, the Japanese version of the McGill Pain Questionnaire, limitation of daily functions, the Hospital Anxiety and Depression Scale, the Eysenck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 31 publications
7
59
1
4
Order By: Relevance
“…Some studies [19][20][21] in the literature assessed depression, anxiety and pain in patients with TMD. Although these studies did not analyze general health indicators, a trend was observed that patients with muscle pain exhibited more psychological problems, poor quality of sleep and a greater number of stress agents.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [19][20][21] in the literature assessed depression, anxiety and pain in patients with TMD. Although these studies did not analyze general health indicators, a trend was observed that patients with muscle pain exhibited more psychological problems, poor quality of sleep and a greater number of stress agents.…”
Section: Discussionmentioning
confidence: 99%
“…The results from approximately 35 published OPPERA studies revolve around the simple phenotype identified by the TMD case definition, indicating that it may be a sufficient marker for underlying complexity as well as suggesting that other diagnostic resources should be allocated to more refined assessment of the appreciable variability reflected as individual differences in how TMDs are expressed. While the OPPERA studies have been limited to subjects 18 to 44 y old characterized on the basis of masticatory system pain, patient characteristics are largely similar across the major RDC/TMD subtypes (Kino et al 2005), and treatment models suggest that the same principles successful for managing pain conditions apply to TMJ impairments (Schiffman et al 2007). Consequently, the OPPERA evidence suggestive of a TMD pain phenotype identified by the core diagnostic variables contained within, for example, the DC/TMD may be generalizable to other types of TMDs but this awaits confirmation.…”
Section: Is There a Tmd Phenotype?mentioning
confidence: 99%
“…These pain scores are higher than those in the literature, usually reported as 3 to 5 on a visual analog scale. 11,12 Treatment of Myofascial pain syndrome is difficult because it may be initiated by peripheral and central mechanisms that appear to be inter-related as Central sensitization would lead to an increased excitability of spinal and supraspinal regions resulting from injury or inflammation-induced activation of peripheral nociceptors. 13 Tizanidine, an alpha-2 -adrenergic agonist, exerts effects in both the brain and spinal cord, with effects at the second order dorsal horn neurons and wide dynamic range neurons-the same location implicated in the central sensitization process.…”
Section: Resultsmentioning
confidence: 99%